On the Reception of the Poem The Twelve by Aleksandr Blok in German Criticism and Literature Studies of the Past 50 Years - Gyöngyösi, Mária (Slavica, 2021)
The article examines the German reception of Alexander Blok’s poem “The Twelve” based on selected criticism and works of literary history published by Slavists, poets and translators during the last fifty years. Analyses and interpretations of the poem are presented in detail, while other post-1917 writings and statements by Blok are also mentioned in order to provide context.